Unveiling the Role of SmartPLS and Technology in Analyzing HR Dynamics for Organizational Effectiveness - Lista Meria; Andriyansah Andriyansah; Felix Sutisna; Alexander William; Lukita Pasha (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2025)
The increasing complexity of organizational environments necessitates a deeper understanding of how management scope and Human Resource (HR) strategies interact to enhance organizational effectiveness. This study examines the integration of management functions and HR practices to address critical gaps in optimizing performance, particularly in dynamic and resource constrained settings. Using the SmartPLS methodology, empirical data was analyzed to evaluate the influence of management scope dimensions and HR strategies on organizational performance. The findings reveal that aligning HR strategies with well defined management functions significantly enhances adaptability, operational efficiency, and employee engagement. Specifically, strategic planning enables organizations to respond effectively to market disruptions, while efficient resource allocation fosters collaboration and productivity. However, challenges such as misaligned priorities, resistance to change, and resource limitations pose significant barriers to successful integration. Addressing these issues through adaptive leadership and innovative management approaches strengthens resilience and promotes sustainable growth. The study underscores the critical role of management HR alignment in leveraging human capital as a competitive advantage. By bridging theoretical frameworks with practical applications, this research provides valuable insights for managers seeking to navigate complex organizational dynamics. The findings highlight the importance of integrating management and HR strategies to foster long term organizational resilience and performance in rapidly evolving business landscapes.